Evaluation of the storage stability of extracellular vesicles - Richter, Maximilian; Fuhrmann, Kathrin; Fuhrmann, Gregor (Journal of Visualized Experiments, 2019)
Extracellular vesicles (EVs) are promising targets in current research, to be used as drugs, drug-carriers, and biomarkers. For their clinical development, not only their pharmaceutical activity is important but also their production needs to be evaluated. In this context, research focuses on the isolation of EVs, their characterization, and their storage. The present manuscript aims at providing a facile procedure for the assessment of the effect of different storage conditions on EVs, without genetic manipulation or specific functional assays. This makes it possible to quickly get a first impression of the stability of EVs under a given storage condition, and EVs derived from different cell sources can be compared easily. The stability measurement is based on the physicochemical parameters of the EVs (size, particle concentration, and morphology) and the preservation of the activity of their cargo. The latter is assessed by the saponin-mediated encapsulation of the enzyme beta-glucuronidase into the EVs. Glucuronidase acts as a surrogate and allows for an easy quantification via the cleavage of a fluorescent reporter molecule. The present protocol could be a tool for researchers in the search for storage conditions that optimally retain EV properties to advance EV research toward clinical application.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Asymmetric flow field-flow fractionation; Bioengineering; Enzyme encapsulation; Exosomes; Extracellular vesicles; Freeze-drying; Issue 147; Lyophilisation; Storage stability